Homo interrogans : questioning and the intentional structure of cognition - Bruin, John, 1956- (Collection Philosophica ;, 2001)
Emerging from the Brentano-Husserl tradition, this volume charts new ground in the conceptual discourse of questioning and answering. John Bruin examines the "logic" of interrogation and makes the case that intentionality itself has the structure of question and answer. Here, he breaks rank with the better known and more traditional and sets out to explore questioning from a phenomenological perspective